Psychosocial factors associated with symptoms of generalized anxiety disorder in general practitioners during the COVID-19 pandemic (2020)
Healthcare providers commonly experience symptoms of anxiety during public health crises and pandemics. The objective of the study was to identify the frequency of symptoms of generalized anxiety disorder (GAD) in general practitioners and to estimate the association with particular psychosocial and demographic factors. This is a cross- sectional study, where a total of 531 general practitioners completed an online form that contained sociodemographic variables, questions about fear and perceptions concerning medical work during the COVID-19 pandemic, 7- Item Generalized Anxiety Disorder Scale (GAD-7), questionnaire on psychosomatic problems and Fear of COVID-19 Scale. The presence of symptoms of GAD was defined by a GAD-7 score of 10 or more points. Voluntary and anonymous participation, acceptance of terms, and informed consent were requested. A p value of <0.05 was considered statistically significant. Symptoms of GAD were identified in 4 out of 10 Colombian general practitioners; the following psychosocial and demographic factors were associated with a greater presence of these symptoms: female gender, social discrimination, anguish, job disappointment, nightmares, stress and other symptoms of fear regarding the pandemic. Conversely, feeling protected by the state or employer, being satisfied with their job as a physician, and trusting government measures and information were associated with a lower presence of symptoms of GAD. These findings highlight the importance of timely psychotherapeutic and psychopharmacological interventions in these individuals. The authors suggest mental health providers should be deployed during times of crisis to decrease the risk of developing mental illness.